2003
DOI: 10.1016/s0378-3782(03)00003-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal alcohol consumption during pregnancy and physical outcomes up to 5 years of age: a longitudinal study

Abstract: Aim: To examine whether alcohol exposure in pregnancy affects weight and head circumference (HC) at birth and 5 years, and whether these effects are independent of cigarette exposure in pregnancy and social disadvantage.Study design: The Mater-University Study of Pregnancy (MUSP) involves a prospective cohort of 8556 mothers who were enrolled at first antenatal visit. The quantity and frequency of alcohol consumption in early and late pregnancy and a measure of binge drinking in early pregnancy were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 52 publications
6
55
1
5
Order By: Relevance
“…A PPROXIMATELY 50 TO 60% OF women in Australia report having consumed alcohol at some stage in their pregnancy (Colvin et al, 2007;O'Callaghan et al, 2003), typically at low or reduced levels (<1 standard drink per day) (Australian Institute of Health and Welfare, 2005;Colvin et al, 2007;Hotham et al, 2008;O'Callaghan et al, 2003). As alcohol use during pregnancy has been associated with a range of adverse outcomes including miscarriage, premature birth, stillbirth, low birthweight, small for gestational age, and fetal alcohol spectrum disorder (FASD), this is cause for concern (Burns et al, 2006;Chudley et al, 2005;Henderson et al, 2007;Jones et al, 1973;Stratton et al, 1996).…”
mentioning
confidence: 99%
“…A PPROXIMATELY 50 TO 60% OF women in Australia report having consumed alcohol at some stage in their pregnancy (Colvin et al, 2007;O'Callaghan et al, 2003), typically at low or reduced levels (<1 standard drink per day) (Australian Institute of Health and Welfare, 2005;Colvin et al, 2007;Hotham et al, 2008;O'Callaghan et al, 2003). As alcohol use during pregnancy has been associated with a range of adverse outcomes including miscarriage, premature birth, stillbirth, low birthweight, small for gestational age, and fetal alcohol spectrum disorder (FASD), this is cause for concern (Burns et al, 2006;Chudley et al, 2005;Henderson et al, 2007;Jones et al, 1973;Stratton et al, 1996).…”
mentioning
confidence: 99%
“…Other studies that found alcohol-associated growth deficits at birth have also not found growth deficits at follow-up [O'Connor et al, 1986;Fried and O'Connell, 1987]. A study of 8,556 pregnancies in Australia also did not find a relation between light and moderate alcohol use during pregnancy and head circumference or weight at birth or at five years of age [O'Callaghan et al, 2003].…”
Section: Results and Discussion The Effects Of Prenatal Exposure To Amentioning
confidence: 91%
“…However, evidence on the impact of occasional or light daily consumption on growth outcomes postnatally is sparse and less consistent; some studies have also shown no association between more moderate drinking levels and postnatal growth/body size (O'Callaghan et al, 2003), but some previous studies have demonstrated height and weight deficits persisting into childhood (Barr et al, 1984;Day et al, 1991Day et al, , 2002Day et al, , 1990Day et al, , 1999. Reasons for conflicting results include dissimilarities in the measurement and classification of exposure to alcohol during pregnancy, follow-up time and analysis differences and population differences where most studies showing an adverse association between light or moderate drinking and growth have been carried out in far more disadvantaged populations than the relatively socially advantaged ALSPAC cohort.…”
Section: Discussionmentioning
confidence: 99%